1999
DOI: 10.1071/a98152
|View full text |Cite
|
Sign up to set email alerts
|

Soil receptivity and host - pathogen dynamics in soils naturally infested with Fusarium oxysporum f. sp. cubense, the cause of Panama disease in bananas

Abstract: Disease severity associated with the pathogen Fusarium oxysporum is generally thought to be proportional to the population of fungal propagules in the soil. However, results from studies using naturally infested soil are contradictory, implicating host predisposition to disease. In this study, soil was amended with chicken manure to investigate the interdependence between the activity and invasiveness of the pathogen, and the incidence of Panama disease in susceptible banana plantlets. Two soil types naturally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 0 publications
3
35
0
1
Order By: Relevance
“…Lady Finger growing on two commercial properties near Currumbin (28°15′S, 153°26′E) in south-east Queensland, Australia. The two properties were known to be infested with race 1 of the pathogen, with only one Vegetative Compatibility Group having been detected (VCG 0125, Pittaway et al 1999). Before use, the soil was coarsely sieved (1 cm 2 grid) to remove plant debris and to break larger soil aggregates.…”
Section: Soil Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Lady Finger growing on two commercial properties near Currumbin (28°15′S, 153°26′E) in south-east Queensland, Australia. The two properties were known to be infested with race 1 of the pathogen, with only one Vegetative Compatibility Group having been detected (VCG 0125, Pittaway et al 1999). Before use, the soil was coarsely sieved (1 cm 2 grid) to remove plant debris and to break larger soil aggregates.…”
Section: Soil Preparationmentioning
confidence: 99%
“…The frequency of invasion of the pseudostem of each plantlet by Foc was calculated using the method of Pittaway et al (1999) with the following modification. After surface sterilisation, the pseudostem/corm tissue was divided into three horizontal regions.…”
Section: Corm Invasion Scorementioning
confidence: 99%
See 1 more Smart Citation
“…The soil was amended at a ratio of 9:1 (v :v) field soil and aged chicken manure (Pittaway et al 1999). Hardwood sawdust (predominantly Eucalyptus maculata and E. crebra) was collected from a local sawmill and composted in a 1-m 3 retaining box for 16 weeks.…”
Section: Soil and Soil Treatment Preparationmentioning
confidence: 99%
“…In a previous study, amending soil naturally infested with Foc with chicken manure was found to increase wilt disease severity in susceptible bananas in the absence of any change in the activity of the pathogen population in the soil (Pittaway et al 1999). In this study the chicken manure effect was used as a reference, to confirm the sensitivity of the activity and invasion bioassays in monitoring changes in pathogen activity and disease incidence, respectively.…”
Section: Introductionmentioning
confidence: 99%